Receptor for advanced glycation endproducts (RAGE) deficiency protects against MPTP toxicity - Teismann, Peter; Bierhaus, Angelika; Nawroth, Peter Paul (Neurobiology of aging, 2012)
Parkinson's disease (PD) is a common neurodegenerative disorder of unknown pathogenesis characterized by the loss of nigrostriatal dopaminergic neurons. Oxidative stress, microglial activation and inflammatory responses seem to contribute to the pathogenesis. The receptor for advanced glycation endproducts (RAGE) is a multiligand receptor of the immunoglobulin superfamily of cell surface molecules. The formation of advanced glycation end products (AGEs), the first ligand of RAGE identified, requires a complex series of reactions including nonenzymatic glycation and free radical reactions involving superoxide-radicals and hydrogen peroxide. Binding of RAGE ligands results in activation of nuclear factor-kappaB (NF-κB). We show that RAGE ablation protected nigral dopaminergic neurons against cell death induced by the neurotoxin MPTP that mimics most features of PD. In RAGE-deficient mice the translocation of the NF-κB subunit p65 to the nucleus, in dopaminergic neurons and glial cells was inhibited suggesting that RAGE involves the activation of NF-κB. The mRNA level of S100, one of the ligands of RAGE, was increased after MPTP treatment. The dopaminergic neurons treated with MPP+ and S100 protein showed increased levels of apoptotic cell death, which was attenuated in RAGE-deficient mice. Our results suggest that activation of RAGE contributes to MPTP/MPP+-induced death of dopaminergic neurons that may be mediated by NF-κB activation.